Trade Policy Challenges in a Small, Open, Fragile, Postconflict Economy: Cambodia - Hal Hill; Jayant Menon (Asian Development Bank (ADB), 2014)
This paper analyzes the World Trade Organization's (WTO) Trade Policy Review: Cambodia, the first completed for the country. The report highlights Cambodia's rapid economic growth after one of the world's worst genocides in the 20th century. This growth has been underpinned by open trade and investment policies in the context of dynamic neighborhood growth effects. The trade regime is mainly tariff-based, with modest inter-sectoral variations in rates. Cambodia has limited trade policy space. It is a signatory to the 10-nation ASEAN Free Trade Agreement, soon to become the ASEAN Economic Community. Moreover, given its long and porous borders with the much larger, dynamic economies of Thailand and Viet Nam, any major cross-border price differences will quickly result in informal trade with these economies, and the People's Republic of China nearby. Most of the country's trade policy challenges are "behind-the-border" issues, a legacy of a generation of civil war and conflict. These include weak bureaucratic capacity, high levels of corruption, poor infrastructure, and limited human capital.
hdl:11540/1281
Keywords: F14; F63; O53; 330; Cambodia; trade policy; ASEAN; globalization; weak institutions